If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3m + -6 + 3m) = 2m Reorder the terms: 2(-6 + 3m + 3m) = 2m Combine like terms: 3m + 3m = 6m 2(-6 + 6m) = 2m (-6 * 2 + 6m * 2) = 2m (-12 + 12m) = 2m Solving -12 + 12m = 2m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-2m' to each side of the equation. -12 + 12m + -2m = 2m + -2m Combine like terms: 12m + -2m = 10m -12 + 10m = 2m + -2m Combine like terms: 2m + -2m = 0 -12 + 10m = 0 Add '12' to each side of the equation. -12 + 12 + 10m = 0 + 12 Combine like terms: -12 + 12 = 0 0 + 10m = 0 + 12 10m = 0 + 12 Combine like terms: 0 + 12 = 12 10m = 12 Divide each side by '10'. m = 1.2 Simplifying m = 1.2
| 6a-9=6+a | | -5p+49=14 | | 5(k-2)=(3k+9) | | x-38+x+98=180 | | 3x-6+6=21+6 | | 7n-19=65 | | 28=x | | k^3-15k^2+5k=0 | | x+1+x-7=90 | | z=8-14i | | V(x)=x(12-2x) | | s=4n^2r^2 | | 8x+67y=5000 | | 19+6b=79 | | 40-r=24 | | 3ax^2=4bx+12 | | h+4.7=10.2 | | 4x+13=22 | | 52-u=10 | | v+v= | | 4=2y+12 | | 74-v=47 | | w^2=3(w+-1) | | c+23=26 | | 5x-(7-x)=6x-7 | | -4+3x=-x+8 | | 9x(-3)= | | 13+6y=23 | | 2=26-4 | | t-21.7=47.1 | | 3+2y=3y-2 | | 6p+13=37 |